Treatment Utilization and Medical Problems in a Community Sample of Adult Women With Anorexia Nervosa - Brodrick, Brooks; Harper, Jessica A.; Van Enkevort, Erin; McAdams, Carrie J. (Frontiers in Psychology, 2019)
Anorexia nervosa (AN) has a prolonged course of illness, making both defining recovery and determining optimal outpatient treatments difficult. Here, we report the types of treatments utilized in a naturalistic sample of adult women with AN in Texas. Participants were recruited from earlier studies of women with AN (n = 28) and in weight recovery following AN (n = 18). Participants provided information about both their illness and treatments during their most severe period as well as during the 2–6 years following original assessments. Based upon their baseline and follow-up clinical status participants were classified as remaining ill (AN-CC, n = 17), newly in recovery (AN-CR, n = 11), and sustained weight-recovery (AN-WR, n = 18). Utilization of health care institutions and providers were compared across groups. There were no differences in groups related to symptoms or treatments utilized during the severe-period. During the follow-up period, intensive outpatient programs were utilized significantly more by the AN-CC group than the other groups, and dietitians were seen significantly less by the AN-WR group. Medical complications related to the ED were significantly more common in the AN-CC group. All groups maintained similar levels of contact with outpatient psychiatrists, therapists, and primary care physicians. Current treatments remain ineffective for a subset of AN participants. Future prospective studies assessing medical health and comorbidities in AN may provide additional insights into disease severity and predictors of clinical outcome.